Studi Transformasi Morfologi Tata Guna Lahan Koridor Braga - Tabitha Hemastuti; Weishaguna (UNISBA Press, 2022)
Abstract. The Braga Corridor experienced physical development from the center of Bandung which resulted in the problem of physical space unity. One of its phenomena is characterized by the presence of dead buildings and conditions of trade and services that have disappeared from their historical existence. From this phenomenon, an issue was obtained, namely the occurrence of problems of physical space unity, especially the morphology of land use in the Braga corridor. Based on the issue, the study question arises, namely